Influence of the use of multiple nutritional claims on South African consumers’ perceptions and purchasing decisions of food products - Van Wyk, Anri (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScFoodSc)--Stellenbosch University, 2021.